Effect of Cameraria ohridella on accumulation of proteins, peroxidase activity and composition in Aesculus hippocastanum leaves - Seliutina, O. V.; Shupranova, L. V.; Holoborodko, K. K.; Shulman, M. V.; Bobylev, Y. P. (Regulatory Mechanisms in Biosystems, 2020)
This study analyzed the dynamics of leaf damage, the content of easily soluble proteins, benzidine-peroxidase activity and the composition of acid enzyme isoforms in the leaves of Aesculus hippocastanum L. under the influence of the chestnut miner Cameraria ohridella Deschka et Dimić (Lepidoptera, Gracillariidae) in plantations in one of the Ukraine’s largest industrial cities Dnipro, located in the steppe zone of Ukraine. During July-August, the destruction of leaves by the pest in relatively stable horse chestnut trees increased to 13.3%, while in unstable trees it increased to 97.5%. The maximum amount of protein was found in horse chestnut leaves in July, which decreased significantly in August and correlated with the level of leaf damage by the pest. The horse chestnut leaves were characterized by a more than twofold increase in cytoplasmic peroxidase activity in cases of high level of damage to the leaves by the phytophage. These observations indicate that consumption of the leaves by C. ohridella causes oxidative stress, which leads to the activation of enzyme. The horse chestnut trees have been shown to respond specifically to the attack of C. ohridella due to changes in the activity of individual peroxidase isozymes, the expression of which varies across the spectrum. In the leaves of the horse chestnut trees with a high level of damage by miner, the expression of enzyme isoforms in the pH range of 4.08–4.15 is significantly activated, which can be considered as a reliable biochemical marker of plant sensitivity of Ae. hippocastanum to phytophagous attack by C. ohridella. However, increase in the degree of phytophage invasion does not change the activity of isoperoxidase 4.21, and isoperoxidase with pI 4.25, 4.42 and 4.58 correspond to a decrease in activity compared with relatively resistant Ae. hippocastanum plants. We noted that the high total activity of peroxidase, as well as active adjustments in the spectrum of the peroxidase system, obviously, contribute to maintaining the functional integrity of the photosynthetic system of leaves of Ae. hippocastanum under the influence of the chestnut miner C. ohridella by neutralizing reactive oxygen species.